Feasibility and Value of Telemedicine Neurosurgical Consultations in a Rural Health System. (16th November 2020) - Rahmani, Redi; Bhalla, Tarun; Susa, Stephen; Proper, Diana; Boulos, Alan S; Shannon, Larry R; Adamson, David C; Bidros, Dani S; Knoop, Henry; Winther, Mark; LeRoux, Peter D
Abstract: INTRODUCTION: Telemedicine has been available for more than 20 years and is playing an increasing role in clinical care. However, few studies have evaluated the value of telemedicine in neurosurgical consultations and in guiding neurosurgical care. METHODS: In this prospective observational study, we examined our experience with emergency video telemedicine consultations for neurosurgical patients at a rural hospital system. Our system uses secure and HIPAA-compliant video conferencing to connect providers and patients to a remote neurosurgery consultant, and operates one out of two days. RESULTS: During a ten-month period, 229 neurosurgical telemedicine consultations were performed. Two-thirds of the patients had intracranial pathology, 28% had spinal pathology and 3% of the consults were for patients who returned after care at our institution or required clearance for another procedure. Five patients required transfer within the hospital system and 12 out of the hospital system for a higher level of care (total 7.4%). Patients that required transfer most frequently had intracranial pathology (70%). The number of patients transferred out was less than in the year before telemedicine was available. CONCLUSION: Telemedicine consultation for neurosurgery is feasible for a variety of neurosurgical pathologies, improves patient access to neurosurgery expertise, and facilitates appropriate transfers to a higher level of care when required. Our findings are especially relevant in light of the COVID-19 pandemic, which has highlighted the importance of delivering quality medical care when physical patient contact is not possible.